Thermal-Stability and Reconstitution Ability of Listeria Phages P100 and A511 - Ahmadi, Hanie; Radford, Devon; Kropinski, Andrew M.; Lim, Loong-Tak; Balamurugan, Sampathkumar (Frontiers in Microbiology, 2017)
The study evaluated the thermal-stability of Listeria phages P100 and A511 at temperatures simulating the preparation of ready-to-eat meats. The phage infectivity after heating to 71 °C and holding for a minimum of 30 s, before eventually cooling to 4 °C were examined. Higher temperatures of 75, 80, and 85 °C were also tested to evaluate their effect on phages thermal-stability. This study found that despite minor differences in the amino acid sequences of their structural proteins, the two phages responded differently to high temperatures. P100 activity declined at least 10 log (PFU mL-1) with exposure to 71 °C (30 s) and falling below the limit of detection (1 log PFU mL-1) while, A511 dropped from 108 to 105 PFU mL-1. Cooling resulted in partial reconstitution of P100 phage particles to 103 PFU mL-1. Exposure to 75 °C (30 s) abolished A511 activity (8 log PFU mL-1) and both phages showed reconstitution during cooling phase after exposure to 75 °C. P100 exhibited reconstitution after treatment at 80 °C (30 s), conversely A511 showed no reconstitution activity. Heating P100 to 85 °C abolished the reconstitution potential. Substantial differences were found in thermal-stability and reconstitution of the examined phages showing A511 to be more thermo-stable than P100, while P100 exhibited reconstitution during cooling after treatment at 80 C which was absent in A511. The differences in predicted melting temperatures of structural proteins of P100 and A511 were consistent with the observed differences in thermal stability and morphological changes observed with transmission electron microscopy.